Age structure and political violence: a re-assessment of the "youth bulge" hypothesis. Issue 1 (2nd January 2019) - Weber, Hannes
ABSTRACT: A popular hypothesis in international studies states that a "youth bulge"––an age pyramid dominated by large cohorts between 15 and 29 years of age––increases the risk of political violence. However, empirical evidence on this link remains inconclusive to date. In this article, we systematically assess the youth effect using new data from 183 countries between 1996 and 2015. We find that within countries, a decrease in the youth ratio is generally associated with a decrease in the number of violent deaths from terrorism or other internal conflicts, and vice versa. This is also confirmed in out-of-sample predictions. However, the association is not evident in all constellations and sensitive to modeling issues. In particular, large cohorts of young males can become a disruptive power in countries that increase enrollment in post-primary education. Although this is usually followed by fertility decline, youth bulges often remain at record levels for quite some time due to high birth rates in the past. Strong labor markets can in general suppress the detrimental consequences of youth bulges. However, the combination of growing youth cohorts and educational expansion often leads to increased political violence even in the presence of low youth unemployment.